Gastrointestinal Manifestations in Children with Primary Immunodeficiencies: Single Center: 12 Years Experience - ÖZEN, AHMET OĞUZHAN; ÇELİKEL, ÇİĞDEM; ERTEM ŞAHİNOĞLU, DENİZ; TUTAR, ENGİN; KALAYCIK ŞENGÜL, ÖZLEM (KARGER, 2019)
Background: It has been reported that 5-50% of patients with primary immune deficiencies (PID) may present with or develop gastrointestinal (GI) manifestations. Objective: This study was aimed at analyzing GI and related endoscopic, histopathological findings in children with PID. Methods: Children with PID who were evaluated by endoscopy between 2005 and 2016 were enrolled in this study. Demographic data, growth parameters, signs and symptoms at diagnosis were obtained. Results: Of 425 children with PID, 195 had GI manifestations. Forty-seven of 195 children required endoscopic investigation, 30 (63.8%) were male, and the mean age was 7.7 +/- 5 years. The rate of consanguinity was 61.7%, and the most common symptom was chronic diarrhea (57.4%). Seventy-two percent of the patients were malnourished. Giardia intestinalis was detected in 4, and Helicobacter pylori was confirmed in 8/45 (17.7%) patients. Non-celiac villous flatting was discovered in 15.5% of patients. Twelve patients were diagnosed as having immunodeficiency associated inflammatory bowel disease (IBD)-like colitis. Conclusions: PID may present with GI manifestations or develop during the course of the disease. Investigating immunodeficiency in patients with atypical GI symptoms can provide an appropriate therapeutic option, and an improved quality of life, particularly in populations with a high rate of consanguinity.
Keywords: Child; Endoscopy; Gut; Histopathology; Primary immunodeficiency; INFLAMMATORY-BOWEL-DISEASE; INTERNATIONAL-UNION; ENTEROPATHY; CLASSIFICATION; DEFICIENCY; DIAGNOSIS; UPDATE